KEEFEKTIFAN MODEL PEMBELAJARAN INQUIRI DALAM KETERAMPILAN MEMBACA TEKS CERITA PENDEK SISWA KELAS III SD NEGERI ERELEMBANG - Inayah, Nurul; Akbar, Amal; Khadijah Razak, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the implementation and effectiveness of the inquiry learning model in improving short story reading skills of third-grade students at SD Negeri Erelembang, motivated by the low level of students’ reading comprehension, particularly in understanding intrinsic elements of the text such as the main idea, theme, moral message, and conclusion. This study employed a quantitative approach using a quasi-experimental method with a One Group Pretest-Posttest Design, involving 20 students as the research subjects. Data were collected through learning outcome tests in the form of pretest and posttest and analyzed using descriptive and inferential statistics through a paired sample t-test. The results showed that the students’ average score increased from 51.15 in the pretest to 84.80 in the posttest, with a learning completeness rate reaching 100%. The hypothesis test results indicated a significance value (Sig. 2-tailed) of 0.000 < 0.05, meaning that there was a significant difference between learning outcomes before and after the treatment. Thus, it can be concluded that the inquiry learning model is effective in improving students’ short story reading skills, as it encourages student activeness, critical thinking, and a deeper understanding of the reading text.